Commission on Sustainable Agriculture and Climate Change—An Overview - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
The new climate Commissioners speak on their hopes for this initiative.